Jordan : Selected Issues and Statistical Appendix. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2004)
This Selected Issues paper and Statistical Appendix on Jordan underlies stabilization and structural transformation of the economy. Current fiscal policy appears to be broadly sustainable and should be sufficient to allow for the continued fall in the debt burden, absent large external macroeconomic shocks. Over the past decade, Jordan has made commendable progress in replacing an informal family-based social safety system with well-defined and well-targeted social protection institutions. The government will need to remain committed to periodic increases of fuel prices to close the gap between domestic and international petroleum product prices.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet